THE UTILIZATION OF MIND MAPPING LEARNING MODELS TO GENERATE DISASTER AWARENESS IN EARTHQUAKE MATERIALS IN CLASS X - Muhammad Alfi; edwar edwar; zairin zairin; warsa sugandi karman (Geographica: Science and Education Journal, 2020)
This study aims to create awareness of disasters in class X students by utilizing the Mind Mapping learning model on disaster material. The method used in this research is descriptive qualitative using literature study analysis. The results obtained from this study are a Mind Mapping learning model that is able to generate awareness of disaster in earthquake material in students. The developed media has never been tested on students so that it becomes a recommendation for further research.